Predictors of newborn admission after labour induction at term: Bishop score, pre-induction ultrasonography and clinical risk factors - Tan, P.C.; Suguna, S.; Vallikkannu, N.; Hassan, J. (Stamford Publishing Pte Ltd / Singapore Medical Association, 2008)
The identification of an unfavourable Bishop score as an independent predictor of neonatal admission is useful in the counselling of women who are considering labour induction.